Risk factors for perioperative blood transfusion in total hip arthroplasty: a meta-analysis - Chenghuan Peng; Lijuan Qiao (BMC Musculoskeletal Disorders)
Abstract Objective The present study assessed and synthesized the potential risk factors for perioperative blood transfusion in total hip arthroplasty from various studies through Meta-analysis. Methods We systematically searched for relevant studies in databases including Web of Science, PubMed, Embase, and Cochrane Library from the time of database creation to 1 February 2025 and included all observational studies exploring perioperative transfusion risk factors in patients undergoing total hip arthroplasty. All included studies were assessed for quality using the Newcastle–Ottawa Scale (NOS) scale. Data were analyzed using Stata 15 software. Results A total of 18 articles (n = 424,158) were included, meta-analysis results suggest that increased intraoperative bleeding [OR = 1.13, 95%CI (1.02, 1.24)], increased postoperative drainage [OR = 2.24, 95%CI (1.24, 4.83)], body mass index ≤ 18.5 [OR = 1.10, 95%CI (1.02, 1.20)], preoperative anemia [OR = 1.82, 95%CI (1.62, 2.03)], age ≥ 80 [OR = 1.49 95%CI(1.21, 1.83)], female [OR = 1.92, 95%CI (1.71, 2.15)], ASA class ≥ 3 [OR = 2.06, 95%CI (1.63, 2.61)] in patients with total hip arthroplasty (THA) increases the incidence of perioperative blood transfusion. Conclusion The results of the current study suggest that increased intraoperative bleeding, increased postoperative drainage, low body mass index (≤ 18.5), preoperative anemia, advanced age (≥ 80 years), female gender, and high ASA classification (≥ 3) were significantly associated with the likelihood of needing blood transfusion. These findings highlight the importance of preoperative risk assessment and perioperative management strategies to reduce the need for blood transfusion and improve patient outcomes.